Efeito do beta-cariofileno na suscetibilidade hepática e renal à aflatoxina B1 em parâmetros bioquímicos, oxidativos e moleculares em ratos - Silveira, Alice Rosa da (2021)
Aflatoxin B1 (AFB1) is a mycotoxin produced manly by Aspergillus flavus and Aspergillus parasiticus fungi. Among the existing mycotoxins, AFB1 has been the most studied due to its high toxigenic potential. Exposure to AFB1 promotes an imbalance in the oxidative and inflammatory system, resulting in damage to different organs. There are still no registered therapeutic interventions against its toxicity. In this context, bioactive compounds that could be consumed naturally in the same meals as the AFB1 contamination is a promising strategy to be studied to reduce the harmful health effects caused by mycotoxin. Thus, the present study investigated the beneficial effects of Beta-caryophyllene (BCP), against AFB1 toxicity in liver and kidney tissues, on biochemical parameters to assess the organic function, tissue oxidation and the immunocontent of cellular pathway proteins involved in antioxidants and inflammatory mechanisms. For this purpose, male Wistar rats were divided into four groups: control; AFB1 (250 μg/kg, i.g.); BCP (100 mg/kg, i.p.) and AFB1 + BCP group. The animals were treated for 14 days, as approved by the Ethics Committee on the Use of Animals at the Federal University of Santa Maria – Annex A. The results showed that exposure to AFB1 caused selective toxicity on the liver tissue, since there were no significant changes in the measured renal parameters. In this sense, AFB1 increased liver injury biomarkers (gamma glutamyl transferase – GGT and alkaline phosphatase – ALP) and reduced levels of non-enzymatic antioxidant defenses (ascorbic acid and non-protein thiol), however did not cause changes in lipid peroxidation levels. Moreover, AFB1 interfered in oxidative pathway regulated by the Kelch-like ECHassociated protein (Keap1)/ nuclear factor (erythroid-derived 2)-like 2 (Nrf2), overacting Glutathione-S-Transferase (GST) activity. Lastly, a main effect of AFB1 on the total interleukin 1 beta (IL-1β) was observed. Remarkably, the associated treatment of AFB1 + BCP improved altered parameters by the mycotoxin. In addition, the BCP and AFB1 + BCP groups showed an increase in the levels of kinase inhibitor of nuclear factor kappa-B subunit beta (IKKβ). Therefore, the frequent consumption of these substances in combination, as well as the effects of AFB1 + BCP treatment presented in this study, reinforce the therapeutic role of the biomolecule against AFB1-induced liver toxicity. In view of this, more research is needed to complement our results.